HOTS-Based Learning on Economic Subjects - Amjad Salong (Universitas Muhammadiyah Mataram, 2021)
This study aims to determine how the implementation of HOTS-based learning in economics subjects. To find out the design of the learning implementation plan (RPP) made by the Economics subject teacher, the learning activities carried out by the Economics subject teacher, to determine the students' higher-order thinking skills, as well as the evaluation and assessment of learning carried out by the teacher at the school. This type of research is descriptive research with a qualitative research model. The subject in this study was a teacher of economics. While the data collection techniques used in this study were in the form of documentation, description tests, interviews, and triangulation. Data were collected by means of observation, interviews and documentation. While the data analysis used a qualitative data analysis approach with an approach by observing the symptoms / activities that were ongoing continuously until it was finished, and the data was at a saturation level. The results of this study indicate that the design of the learning implementation plan made by the economics subject teacher has met the criteria for higher-order thinking, the implementation of learning activities by the subject teacher has implemented learning activities that lead to higher-order thinking skills, as well as evaluation and learning assessment has shown an element of measurement of higher order thinking.